Breaking the general practice‐hospital divide: Engaging primary care practitioners in multidisciplinary cancer care. Issue 5 (9th September 2020) - Fairweather, Luke; Tham, Nicole; Pitcher, Meron
Abstract: Aims: To integrate primary care into multidisciplinary cancer meetings and improve communication between hospital‐ and community‐based care providers. Methods: A 12‐week pilot study was conducted at Western Health, implementing a model of care, where two general practitioners (GPs) were recruited from the local community to attend weekly breast and lung multidisciplinary meetings in a liaison role as a primary care representative (PCR). Community GPs and hospital specialists were surveyed at the end of the study to assess the impact of this model of care. Results: All stakeholders agreed that two‐way communication between hospital‐ and community‐based care was improved. The role of the PCR enabled better engagement of GPs in cancer care, allowing them to manage their patients with more confidence. Patient information contributed by GPs provided a wider context for hospital specialist treatment planning and decision making. Conclusion: This project has demonstrated an effective model to integrate primary care practitioners in multidisciplinary cancer care, as it enables timely and relevant two‐way communication between the community and hospital care. Abstract : This pilot study demonstrated an effective model of care where general practitioners were recruited from the local community to attend weekly multidisciplinary cancer care meetings in a liaison role. Integrating primary care practitioners enabled timely and relevant two‐way communication between the community and hospital care.